Applications of Recombinant Dna Technology in Gastrointestinal Medicine and Hepatology: Basic Paradigms of Molecular Cell Biology. Part B: Eukaryotic Gene Transcription and Post-Transcripional Rna Processing - Gary E Wild; Patrizia Papalia; Mark J Ropeleski; Julio Faria; Alan BR Thomson (Canadian Journal of Gastroenterology)
The transcription of DNA into RNA is the primary level at which gene expression is controlled in eukaryotic cells. Eukaryotic gene transcription  involves several different RNA polymerases that interact with a host of transcription factors to initiate transcription. Genes that encode proteins are transcribed into messenger RNA (mRNA) by RNA polymerase II. Ribosomal RNAs (rRNAs) and transfer RNAs (tRNAs) are transcribed by RNA polymerase I and III, respectively.  The production of each mRNA in human cells involves complex interactions of proteins (ie, trans-acting factors) with specific sequences on the DNA (ie, cis-acting elements). Cis-acting elements are short base sequences adjacent to or within a particular gene. While the regulation of transcription is a pivotal step in the control of gene expression, a variety of molecular events, collectively known as ’RNA processing’  add an additional level of control of gene expression in eukaryotic cells.